'A great adventure in both teaching and learning': Teacher identity and innovative responsible management education pedagogies in Business Schools - Radclyffe-Thomas, N.; Schmitz, M.; Breitbarth, T.; Miandar, T.; Pietrzak, M.; Sebhatu, S. P.; Simaens, A. (International Journal of Management Education, 2025)
This self-reference case study reports on applying teacher identity as a lens to examine the intentions and experiences of a group of business school pedagogy experts convened from the eight European regional chapters of the United Nations initiative Principles for Responsible Management Education (PRME) to support the Impactful Five (i5) project as an Expert Pedagogy Group (ExPeG). This paper introduces PRME, the i5 project in general and the concerted European approach. We discuss how Education for Sustainable Development (ESD) has demanded the need for innovative teaching, setting out some thoughts on the role of management educators as leaders and the concept of teacher identity and how these might link to the establishment of Communities of Practice (CoP) in the context of contemporary management education. Against this backdrop, we offer a snapshot of the teacher identity of educators heavily involved in an innovative ESD project over a period of approximately two years from 2022 to 2024, examining what motivates busy Business School teachers to join voluntary Responsible Management Education (RME) pedagogic initiatives and what, if any, impact does involvement with PRME i5 have on teachers’ professional identity.